Aplikasi Traveloka sebagai Bentuk Konstruksi Sosial dalam Dunia Siber (Faculty of Communications Science, Dr. Soetomo University, 2019)
Technology is a things that can not be separated from human life today. Technology is present as a medium of information and communication for human. Living in a digital world where technology is developing so rapidly gave a new technologies that make human activity more easy and faster. New media technologies created in society are inseparable from social constructions in societies where the technology is formed from human needs for new things that can help their daily activities. Traveloka as a form of social construction in cyberworld would like to illustrate that the presence of Traveloka application as a new media technology has answered the human need for easy information about travel services. Traveloka application with all advances in technology provides a transportation information, hotels, entertainment, and information about tourist destinations. Traveloka was born as a new media in cyberworld which make use of technological sophistication as responses of human needs. Keywords: Technology, New Media, Social Construction, Cyberworld, Traveloka